Efficacy Of Doramectin Against Sarcoptic Mange In Camels - Saxena, A.D.; Undirwade, S.C.; Devi, Sarita; Padhiyar , A.P.; Panchasara , H.H. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A total of four camels aged between seven to eight years were presented to the College Clinics with a history of inappetance and intense itching around neck, inguinal and perineal regions. Based on skin scrapping examination and clinical signs, mange infestation of Sarcoptes scabei was confirmed. Successful therapeutic management was done with the use of doramectin @ 0.2 mg/ kg b.wt. s/c along with supportive therapy. Complete recovery and disappearance of mites from skin scrapping was noticed for all four camels after four weeks.